The functional movement screen and abdominal muscle activation in the prediction of injuries in high school cricket pace bowlers - Martin, Candice (My University, 2017)
This research makes a meaningful contribution to the development of effective injury prevention strategies among adolescent cricket pace bowlers. This dissertation, specifically investigated two screening procedures, the Functional Movement Screen (FMS) and ultrasound measured abdominal wall muscle thickness, both of which aim to predict injury among the general and sporting population. More specifically, the dissertation investigated the applicability of these screening procedures to adolescent cricket pace bowlers. Adolescent pace bowlers are prone to injury due to the high load and complex nature of the bowling action as well the risk factors associated with the adolescent growth spurt. Studies related to the validity of the FMS in terms of the prediction of injuries among various sporting disciplines have been conducted but none among cricket pace bowlers. Studies related to the association between abdominal wall muscle morphometry (i.e. thickness at rest and during the performance of abdominal drawing in manoeuvre (ADIM), as measured by ultrasound imaging (USI), and injury among professional and amateur cricket pace bowlers have had conflicting results and limited research related to abdominal muscle morphometry among the adolescent pace bowlers exist. Adolescent pace bowlers that were injury free at the start of the season were recruited for this study. Details related to the nature of past injuries as well as injuries sustained during the season were monitored and recorded over a three month period. Included in this dissertation are three original papers. The first two investigated the association between prospective in-season injury and the two above mentioned screening procedures. The third investigated the concurrent validity of FMS overhead deep squat (DS) when observer rating was compared to kinematic analysis. The first paper (Chapter 4) investigated the association between muscle morphometry of transverse abdominis (TA), internal oblique (IO) and external oblique (EO), as measured by USI, at the start of the season and in-season injury. Results indicated that non-dominant internal oblique is thicker than dominant IO (p=0.01, effect size (ES) =0.65) in injury free pace bowlers but that non-dominant and dominant internal oblique (p=0.47; ES=0.24) is symmetrical in injured pace bowlers. Based on these findings we concluded that asymmetry in IO thickness may play a protective role against injury rather than being a predisposing risk factor to injury. The second paper (Chapter 5) investigated the association between pre-season total FMS score and in-season injury among adolescent pace bowlers. Results indicated that there was no significant difference in total pre-season FMS scores of bowlers that sustained injuries during the season and those that remained injury free (p=0.58). Also, a total FMS score of 14 (the score previously found to be an accurate cut-off score) does not provide the sensitivity needed to assess injury risk among adolescent pace bowlers. It was therefore concluded that the FMS was not associated with in-season injury among adolescent pace bowlers and that the usefulness of this tool in the prediction of injuries among these cricketers is doubtful Paper 3 (Chapter 7) investigated the concurrent validity of the overhead DS included in the FMS when observer rating is compared to kinematic analyses. The FMS attempts to systematically score the quality of movements, among other the DS, based on specific criteria. The developers of the FMS suggest that specific mechanics related to the DS differ between levels of scoring. There were significant differences in the degree to which the torso was flexed forward, away from the vertical (p=0.03), where groups 3 and 2 (i.e. those participants who scored a rating of 3 and 2 respectively for the performance of the DS) remained more upright compared to Group 1. There was also a significant difference in the degree to which the femur passed the horizontal line (p=0.05) between the three groups. At the point of deepest descent, the femurs of Groups 3 and 2 were below the horizontal while that of Group 1 remained above. The findings of this part of the study suggest that, while raters correctly identified differences in biomechanics between groups for two of the scoring criteria (femur below horizontal and feet remaining flat on floor or board) , they did not rate the groups correctly for the remaining criteria. The concurrent validity of the observer rating of the FMS DS is therefore questionable. In conclusion, the high load nature and complexity of the pace bowling action together with the intrinsic risk factors related to the adolescent growth spurt, expose school boy cricket pace bowlers to injury. The ability of these screening procedures to accurately identify individuals at risk of sustaining injuries are therefore of the utmost importance. Despite the popularity of the FMS, the concurrent validity of this screening tool and its lack of association with in- season injury among adolescent pace bowlers brings the use of FMS into question. Symmetry, not asymmetry, of the IO and under-, not over-activation of the dominant TA muscles were associated with in-season injuries among pace bowlers. All of the above conflicting findings pose uncertainty regarding the applicability of these screening procedures to injury prediction among adolescent cricket pace bowlers.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg, 2017
Keywords: Abdominal Muscles Injuries